The Relevance of Constructivist Learning Theory to the Application of Independent Learning - Azizatul Afifah; Romi Febrianto; Charles (Yayasan Pendidikan Genlita Indonesia, 2024)
This article aims to improve understanding of the relevance between constructivist theory and the implementation of the Independent Curriculum in Indonesia. This study uses a literature study method to describe the relationship between Construsivistic theory and the Independent Curriculum. The analysis results show that three things generally reflect the relevance between the two. First, implementing the Independent Curriculum can increase social interaction in learning, in line with the Constructivistic emphasis on the role of social interaction in the knowledge construction process. Second, the role of teachers in the Independent Curriculum as facilitators and companions (scaffolding) supports the Constructivist concept of students' actual and potential development zones. Third, the Independent Curriculum provides opportunities for developing students' social skills by strengthening the Pancasila Student Profile through the view of Constructivist Theory regarding the importance of the social environment in shaping children's social and cognitive abilities. Further research is recommended to investigate empirical evidence regarding the effect of project-based learning on the implementation